Optimization and Development of an Efficient 13 X-STRs Multiplex PCR System for Paternity Testing : 13 X-STRs Multiplex PCR System - Tariq, Muhammad Akram; Tahir, Mohammad Ashraf (Pakistan Journal of Health Sciences, 2023)
X-chromosomal short tandem repeats (X-STRs) markers complement autosomal STR identification systems and valuable tools in complex kinship cases. Objective: To develop a multiplex PCR system that consists of 13 X-chromosome STR markers, including GATA172D05, DXS8378, DXS6801, DXS6793, DXS6810, DXS7132, GATA31E08, DXS9902, HPRTB, DXS6789, DXS7423, DXS8377, DXS981 and sex-determining locus Amelogenin. Methods: Primer sequences of all X-STR markers were acquired from the Genome databases, and the original sequences for HPRTB, DXS6789, DXS7423, DXS8377 and DXS981 were modified to eliminate primer-dimer formation and optimize melting temperatures to increase annealing efficiency. All primer pairs were labelled with fluorescent dyes to support amplification in a multiplex PCR, and the cycling conditions for multiplex PCR were optimized. Alleles for each locus were bi-directionally sequenced to determine the exact repeat size, and alleles generated in multiplex reactions were undistinguishable from alleles produced in a single marker PCR reaction. Results: The combined power of discrimination of 13 X-STRs was 2.96 x 10-13 and 2.58 x10-8 in females and males, respectively. Conclusions: In conclusion, we have developed a 14-plex PCR system that can potentially be used for parentage testing and forensic casework studies.